Rhizobacteria profiling of endemic aromatic rice Pulu Mandoti from Enrekang, South Sulawesi, Indonesia through shotgun metagenomic - ANDI MASNIAWATI; BASO MANGUNTUNGI; MUHAMMAD RUSLAN UMAR; NURHIKMAH NURHIKMAH; ARLINDA PUSPITA SARI; ANNISA SURYASETYA SALSABILA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Masniawati A, Manguntungi B, Umar MR, Nurhikmah, Sari AP, Salsabila AS. 2025. Rhizobacteria profiling of endemic aromatic rice Pulu Mandoti from Enrekang, South Sulawesi, Indonesia through shotgun metagenomic. Biodiversitas 26: 3183-3192. Pulu Mandoti is an indigenous rice with a unique aroma, texture, and cultural significance in local communities. The rhizosphere microbial community plays a pivotal role in supporting its growth, nutrient cycling, and stress resilience. Understanding the microbial diversity associated with Pulu Mandoti rice is essential for developing strategies to improve its cultivation and conservation. Therefore, this research aimed to conduct a comprehensive analysis of rhizobacteria profile of Pulu Mandoti through shotgun metagenomic. The research methods include soil analysis, DNA extraction, and shotgun metagenomic analysis. Shotgun metagenomic sequencing reported a diverse microbial community dominated by bacteria, with Proteobacteria (42%) as the most abundant phyla, and Alphaproteobacteria (15%) in the class. In the family level, Anaeromyxobacteraceae and Bradyrhisobiaceae were particularly abundant. The genus Bradyrhizobium within Bradyrhisobiaceae showed the highest richness, with 97 species. Anaeromyxobacter, such as Singulisphaera and Rhodoplanes dominated the species at 66% and 83%, respectively. This microbial profiling showed the intricate relationship between Pulu Mandoti rice and the rhizospheric microbiome, emphasizing the role of microbial diversity in supporting growth and resilience. It’s essential for offering potential applications for sustainable agriculture and crop optimization.